Advancements in Intelligent Systems: Transforming Engineering Applications - Rudresh Shirwaikar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Intelligent systems, powered by artificial intelligence and machine learning techniques, have revolutionized various domains, including engineering applications. This paper explores the significant advancements in intelligent systems and their transformative impact on engineering practices. It examines how these systems have enhanced efficiency, accuracy, and innovation across diverse engineering disciplines. Through case studies and examples, this paper illustrates the evolving landscape of intelligent systems and their profound implications for the future of engineering